Mimi the selfish kitten : a book about sharing our toys. (Asia : Time Life Asia, 1997)
Mimi the kitten is selfish and doesn't like sharing her toys. When her friends run off to play without her, Mimi is left alone. She soon finds out that being selfish is not much fun . . .
w/ casette tape
Keywords: Values; Sharing - Fiction